Waste of a nation : garbage and growth in India - Doron, Assa; Jeffrey, Robin (Harvard University Press, 2018)
"Why is India so filthy?" This book draws on four years of research by an anthropologist and historian to tease out reasons for India's public-sanitation agonies. From the days of Mahatma Gandhi to Prime Minister Narendra Modi, India has struggled with garbage and human excrement. In the twenty-first century, the problems grow urgent as an urbanizing middle class expands, consumes, excretes and throws things away at increasing rates. In 2014, the new Modi government began to invest hundreds of millions of dollars in a Clean India! or Swachh Bharat! campaign to change habits, build toilets, purify water and tame domestic, industrial and medical waste. The authors argue that many of India's problems were shared by other countries over the past 150 years and that India can benefit from such experience and the science of the digital world. But two challenges are unique and formidable. First, the density of population is surpassed only by Bangladesh. India has less space in which to dump its huge volumes of waste than any major country in history, including China. The second obstacle lies in ideas and prejudices relating to caste. Some people are born into castes (once called "untouchables") that are still widely regarded as tainted by birth and associated with foul and demeaning tasks. Such attitudes reinforce NIMBY attitudes found throughout the world. India's diversity, however, means that throughout the country the efforts of women and men from waste-pickers to executives demonstrate exceptional achievements in dealing with waste, though they provide no single recipe for a Clean India.--